The Role of Accountability In Determining The Relationship Between Quality Of Financial Reporting And Performance Of Public Organizations (Case Study on SKPD Boyolali) - Dwi Ratnajati; Zulfikar Zulfikar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Government financial reports are useful as a medium of public accountability for accounting for the use of resources and the implementation of policies entrusted to the government by the public in order to achieve the goals that have been set. The purpose of this study is to determine the role of accountability in determining the relationship between financial reporting quality and public organization performance. This study relies on primary data. The total sample size in this study was 91 samples drawn at random. Using descriptive statistical analysis techniques, hypotheses were tested. According to the findings of this study, accountability plays a mediating role in the relationship between the quality of financial reporting and the performance of public organizations, which has significant implications for public organizations that want to improve the quality of financial reporting and organizational performance through a better accountability system. One concrete effort to achieve financial management accountability is the submission of financial accountability reports that are timely and prepared in accordance with generally accepted government accounting standards. Keywords: Accountability, Quality of Financial Reporting, Performance of Public Organizations, Boyolali SKPD